Pedagogical innovation: enhancing higher order thinking skills of pre-service teachers through collaboration in school-based experience - Ahmad, Nor Aniza; Abdul Majid, Norliza; Azis, Mohd Isa (IATED Academy, 2015)
The aim of this study is to enhance the skills of preservice teachers in understanding the theory of cognitive development in children through collaboration with school in School Based Experience Program (SBE). The study involved 48 preservice teachers who enrolled in a compulsory course EDU 3102 Child Development, which is a basic professionalism course taught at Malaysian Institute of Teacher Education. The methods used to collect data were observation, interviews, questionnaires and self-reflective writing. The result of this study showed that school collaboration had improved the level of understanding of children's cognitive development theory among the preservice teachers. Additionally, they had also gained valuable experience during their involvement in school based experience program (SBE). The program had enable them to document the physical and cognitive development of children of 6 to 7 years of age. The program has strengthened the knowledge and skills of the preservice teachers on theoretical and practical aspects of child development.